2-Aminoisoindoline-1, 3-Dione-Functionalized Fe3O4/Chloro-Silane Core-Shell Nanoparticles as Reusable Catalyst: An Efficient Heterogeneous Magnetic Nanoparticles for Synthesis of 4H-Pyran Derivatives through Multicomponent Reaction. (9th August 2022) - Shabani, Nemat; Heravi, Mohammad Reza Poor; Babazadeh, Mirzaagha; Ghasemi, Elnaz; Amini, Mojtaba; Robertson, Craig
Abstract: 2-Aminoisoindoline-1, 3-dione functionalized by Fe3 O4 @chloro-silane core-shell nanoparticles, then a green and convenient approach for the synthesis of a series of 4 H -pyrans by the reaction of aryl aldehydes, malononitrile and methyl acetoacetate in ethanol/60 °C under by using magnetic nanoparticles (MNPs) of Fe3 O4 @SiO2 -NH-isoindoline-1, 3-dione is described. The characterization was performed by using a variety of conventional analytical instruments such as Fourier transform infrared spectra, field emission scanning electron microscopy, transmission electron microscopy, vibrating sample magnetometer, thermal analysis. This method provides several advantages such as environmental friendliness, shorter time, excellent yields, easy separation of MNPs with using of external magnet and simple work-up procedure.